Hi,

having trouble with arranging formulae that have a negative sign. i.e.

a - bx = m

- bx = m - a

x = [m - a][/-b]

thats my working of the problem

but the text book answer is: x = [a - m][/b]

what am I doing wrong?

Printable View

- Mar 21st 2009, 07:29 PMnativecatformula rearrangement
Hi,

having trouble with arranging formulae that have a negative sign. i.e.

a - bx = m

- bx = m - a

x = [m - a][/-b]

thats my working of the problem

but the text book answer is: x = [a - m][/b]

what am I doing wrong? - Mar 21st 2009, 07:57 PMProve It
You haven't done anything wrong.

Remember that $\displaystyle p - q = -(q - p)$ and that a negative times/divided by a negative gives a positive.

So from your working you've ended up with

$\displaystyle x = \frac{m - a}{-b}$

$\displaystyle = \frac{-(a - m)}{-b}$

$\displaystyle = \frac{a - m}{b}$.